Radiobiology for the radiologist - Hall, Eric J (Wolter Kluwer, 2019)
Considered the “gold standard” in the field for over 45 years, Radiobiology for the Radiologist combines traditional and molecular radiation biology principles and appeals to students, residents, and veteran clinical practitioners. This edition continues the two-part format of previous editions and features brand-new chapters, thoroughly updated content, and hundreds of figures that provide a visual context to the information in each chapter.